Gender Differentials in Level of Use of Vitamin Supplements among Non-Academic Staff of Tertiary Institutions in Benue State - Mnyamchie, Francisca Doom; Burbwa, Sarah Ngukuran; Zwawua, Orfega (International Journal of Human Kinetics, Health and Education, 2023)
This study investigated the level of use of vitamin supplements among the non-academic staff of tertiary institutions in Benue State. A cross-sectional descriptive survey research design was adopted for the study. The population for the study comprised all non -academic staff of tertiary institutions in Benue State. A multi-stage sampling procedure was used to select 300 non-academic staff from a population of 3,956 staff. The instrument for data collection was a self-developed Vitamin Supplement Use Questionnaire (VSUQ) which was validated by three experts, with a reliability index of 0.92. Mean and standard deviation were used to answer the research questions, while independent t-test was used to test hypothesis at .05 level of significance. The results indicated higher level use of vitamin supplements among females than their male counterparts (females M = 2.22 ± 0.84 > males M = 2.11 ± 0.87). Further statistics revealed that there was no statistically significant gender difference in the level of use of vitamin supplements (p > .05). The authors recommended that health committees in the tertiary institutions in Benue State to embark on enlightenment programmes for the safe use of vitamin supplements on the part of the staff so as to enhance their health status